Grecità di Sicilia: il caso defixiones. Un nuovo testo da Selinunte (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2012)
The epigraphic documentation from Selinous is one of the hugest of the archaic period, together with the records from Gela and Camarina; defixiones represent a significant specimen, not only for epigraphic and linguistic aspects, but also for the light we can shed on what we can learn about the “magic” texts employed in everyday life. After a brief presentation of the characteristics regarding public and private life a new inscription from Selinous is presented and discussed.